Dari Greenwashing ke Dampak Nyata: Menilai Kembali Integrasi Pemasaran-Komunikasi untuk SDGs Melalui Analisis Bibliometrik Berbasis PRISMA. - Aldino, Helmi Prilla (Jurnal Salingka Nagari, 2026)
This research investigates the integration of digital marketing strategies and sustainability communication in supporting the achievement of the Sustainable Development Goals (SDGs) through Systematic Literature Review (SLR) and bibliometric analysis. The main findings reveal three critical aspects, namely: (1) the effectiveness of the phygital approach (combined physical-digital) in increasing consumer engagement by up to 2.3 times, especially in Goal 12 (responsible consumption) and Goal 13 (handling climate change); (2) the paradox of digital sustainability where 68 persen of studies ignore the environmental impact of digital marketing activations such as server emissions and e-waste; and (3) the implementation gap between multinational companies and MSMEs, with only 22 percent of Indonesian MSMEs consistently adopting green principles. The methodology used combines the modified PRISMA protocol with local literature handsearching to reduce geographic bias, complemented by VOSviewer analysis validated through expert judgment. The results of the bibliometric mapping show emerging trends such as AI-driven sustainability and green algorithms that have not been widely explored in the context of the Global South. In practical terms, this study recommends, among others: the development of the Digital Sustainability Index as a tool to measure the impact of campaigns, a triple helix collaboration between the government-digital platforms and academics to develop green performance-based fiscal incentives, and the adaptation of the Singapore SkillsFuture model in the vocational education curriculum. The main theoretical contribution lies in integrating Stakeholder Theory with the fifth-generation Integrated Marketing Communication (IMC) framework, as well as identifying future research agendas on algorithmic bias in sustainability message delivery.